Efficiency improvement of inverted perovskite solar cells enabled by PTAA/MoS2 double hole transporters. (13th August 2022) - Hu, Weidong; Jin, Xin; Li, Aijun; Liu, Cheng-Liang; Wang, Xiao-Feng
Abstract: Hole transport layer (HTL) plays a critical role in perovskite solar cells (PSCs). We focus on the improvement of PSCs performance with MoS2 nanosheets as the anode buffer layer in the inverted photovoltaic structure. PSC with single MoS2 buffer layer shows poor performance in power conversion efficiency (PCE) and the long-term stability. By combination of MoS2 and Poly[bis(4-phenyl) (2, 4, 6-trimethylphenyl) amine] (PTAA) as double-layer HTL, the PCE is improved to 18.47%, while the control device with PTAA alone shows a PCE of 14.48%. The same phenomenon is also found in 2D PSCs. For double-layer HTL devices, the PCE reaches 13.19%, and the corresponding PCE of the control group using PTAA alone is 10.13%. This significant improvement is attributed to the reduced interface resistance and improved hole extraction ability as shown by the electric impedance spectroscopy and fluorescence spectroscopy. In addition, the improved device exhibits better stability because the PCE still maintains 66% of the initial value after 500 h of storage, which is higher than the 47% of the remaining PCE from device based on single PTAA or MoS2 . Our results demonstrate the potential of polymer/inorganic nanomaterial as a double-layer buffer material for PSCs.